Segmentacja rynków europejskich ze względu na rozwój społeczeństwa informacyjnego - Sobczak, Elżbieta (Segmentation of the European Union markets with regard to the information society development, 2005)
The objective of the hereby elaboration is the segmentation of the European Union markets and the candidate countries, with regard to the information society development. The segmentation comprises changes, which have been taking place under the influence of modem teleinformation technologies. The carried out segmentation is of dynamic character, considering not only the level but also the speed at which information economy keeps developing. Time span of the research covers the years 1998-2003. The following, among others, measurement factors have been considered: numer of personal computers, Internet hosts, Internet users, expenditure on information technologies, etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 191-203